Resiliensi dan Kerbelanjutan dalam Krisis: Praktik-praktik Ketahanan Desa Wisata Tinalah Pasca-Pandemi: Resilience Practices of Tinalah Tourism Village Post-Pandemic - Saadah, Nailis Manan; Eddyono, Fauziah (Journal of Applied Management Research, 2025)
This study analyzes resilience strategies and multi-stakeholder collaboration in the post-pandemic recovery of Tinalah Tourism Village. Employing a descriptive qualitative approach and an intrinsic case study design, data were collected through in-depth interviews and thematically analyzed using NVivo 12 Plus. The findings reveal that the local community demonstrated adaptability through human resource capacity building, digitalization of tourism promotion and services, and diversification of culture- and environment-based tourism products. Strategic collaboration with government bodies, academic institutions, and digital platforms supported recovery efforts without compromising community autonomy. The application of sustainable tourism principles and data-driven governance enhanced the destination’s resilience. Tinalah Tourism Village exemplifies how a community-based tourism village can recover independently and sustainably from a crisis, offering a replicable model for other regions facing similar challenges.